Assessment of the Systemic Immune-Inflamation Index and its Association with Morbidity and Mortality in Critical Pediatric Patients (Revista de Medicina Clinica, 2024)
Introduction: There are several scales and biomarkers to measure the severity of pediatric disease, but some are expensive and not very accessible. The systemic inflammation index-immunity (SII) is considered a promising biomarker due to the relationship between the systemic inflammatory response and humoral and cellular imbalance. The aim of the study was to describe the values of the IIS upon admission to the PICU of the Hospital Universitario “Dr. José E. González” and his association with morbi-mortality. Patients and methods: Cross-sectional, descriptive, observational, retrospective study. Patients admitted to the PICU of the Hospital Universitario “Dr. José E. González” from 2018 to 2020. The following data were collected: age, sex, comorbidities, days of mechanical ventilation, days of stay in the PICU, PELOD-2 and PRISM III score, mortality. IIS was calculated in the admission blood count. The values obtained were described and the values were analyzed with the associated variables. Results: Our study included 86 patients, of whom 57% were male, 46.5% were patients between 6 and 11 years old, and 53.5% between 12 and 15 years old. Most of the patients were admitted for a neurosurgical pathology. The median score on the IIS was 592.5 x109. PRISM-III and PELOD-2 scores were not related to IIS value. We did not find a good predictive value for the days of hospital stay and mechanical ventilation, or for mortality. Conclusion: The IIS does not seem to be related to the prediction of outcomes or to other scales used to measure disease severity.
Keywords: Neutrophil; Lymphocyte; Systemic inmune-inflammation index; Shock; Child